Professional Accountability for Improving Life, College, and Career Readiness - Jon Snyder; Travis Bristol (Arizona State University, 2015)
This article builds on Darling-Hammond, Wilhoit, and Pittenger's (2014) new paradigm on Accountability for College and Career Readiness by focusing on one of its three pillars-professional accountability. The article begins by offering a conceptual framework for professional accountability for improvement. Next, it highlights slices of four organizations whose improvements efforts serve as a model for professional accountability. Then the article provides an overview of what a complete system of professional accountability would require. The article ends with a narrative of a teacher's career in an imagined future where school, district, state, and federal contexts are designed and provide resources for a cohesive constellation of policies, programs, and practices that increase learning for children, adults and the entire system.